Statistical Analysis of Protection Current Transformer Performance Based on Error Ratio and Knee Voltage on 20 kV Feeder at Bangka Transmission and Substation Service Unit - Sapitri, Maisa; Asmar, Asmar; Yandi, Welly; Kurniawan, Rudy (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2025)
Current Transformers (CTs) are essential components in power system protection, ensuring accurate current measurement for relay operations.. This study evaluates the accuracy of protection CTs used in 20kV feeders at the Bangka Transmission and Substation Service Unit. Measurements were conducted on CTs with 5 and 7 years of usage to analyze ratio error and knee voltage compliance with IEC 61869-2 standards. The results indicate that all CTs meet the standard, with ratio errors below 1% and knee voltages exceeding 60V. Normality tests confirmed that the data are normally distributed, allowing statistical analysis using t-tests. The t-test results showed no significant difference in ratio error and knee voltage between CTs used for 5 and 7 years. This study concludes that aging over this period does not significantly affect CT accuracy, ensuring continued reliability in power system protection.